Abdominal wall endometriosis in the caesarean section surgical scar- a case report - Trivikrama, Heera Shenoy; ., Shivakumar; Sajitha, Ambichi Kuniyil; Chandni, Sabarmathi; Geethanjali, Remesh; Lavatt, Deepak; Nidhi, Naduvithiyil Thundikandi; Singh, Mary Nandini; Shamla, Padincharayil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Scar endometriosis is the presence of endometrial tissues with glands in the previous incision or scar. Its overall estimated incidence after post-caesarean and post-hysterectomy is 0.03-0.4% and 1.08-2%, respectively. The patient presents with non-specific symptoms such as cyclical abdominal pain at the site of a previous surgical incision and an abdominal lump with a cyclical increment in size, which is tender. The diagnosis is made only after the surgical excision with confirmation by histopathological analysis. We present the case of a 30-year-old P2 L2 complaining of cyclical abdominal pain and a lump on the right side of a Pfannenstiel incision. She had undergone two lower segment caesarean sections (LSCS); the last surgery was five years ago. She conceived and at 38.2 weeks an elective caesarean with concurrent sterilisation and excision of scar endometriosis with mesh repair was done. After the surgical excision, the sample was sent for histopathological examination, and scar endometriosis was confirmed.